2022
DOI: 10.1103/physrevd.105.086014
|View full text |Cite
|
Sign up to set email alerts
|

Quantum gravity corrections to the matter dynamics in the presence of a reference fluid

Abstract: We analyze the effect induced on standard quantum field theory (in a functional approach) by quantum gravity corrections to a pure classical background. In the framework of the Kuchař and Torre proposal for a gravity-matter theory constrained to a Gaussian reference frame, materialized as a fluid in the system evolution, we consider a Born-Oppenheimer separation of the system, regarding the gravity degrees of freedom as the slow varying component and the matter plus the Gaussian fluid as fast quantum coordinat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…Furthermore, it was shown that the cases (g + = 1, g − = 0) and (g + = 0, g − = 1) correspond to an extension of general relativity that includes solutions corresponding to an additional effective pressureless perfect fluid matter source. Interestingly, such a matter source has been of prior interest as a possible solution to the problem of time in quantum gravity [25,27,[30][31][32]. We find it encouraging that in the present models, the perfect fluid arises 'naturally' from the theory and does not have to be independently posited.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Furthermore, it was shown that the cases (g + = 1, g − = 0) and (g + = 0, g − = 1) correspond to an extension of general relativity that includes solutions corresponding to an additional effective pressureless perfect fluid matter source. Interestingly, such a matter source has been of prior interest as a possible solution to the problem of time in quantum gravity [25,27,[30][31][32]. We find it encouraging that in the present models, the perfect fluid arises 'naturally' from the theory and does not have to be independently posited.…”
Section: Discussionmentioning
confidence: 58%
“…When the fields are complexified, they become genuinely independent objects. Equation (31) defines the property of selfdualness (here F +IJ ) or anti-self-dualness (here F −IJ ). It is possible to parameterize a self-dual or anti-self-dual Lorentz tensor in terms of a field E I as follows:…”
Section: Local Lorentz Symmetry In Gravitation and Its Complexificationmentioning
confidence: 99%
“…Thus, the wave function is presented as a product of gravitational and matter wave functions. According to another assumption accepted in [9], the energy of matter fields is much smaller with respect to the energy of gravity, and the gravitational wave function must satisfy constraint equations for pure gravity. In this approach, one obtains equations for pure gravity in each order of expansion, but not only in the order O(M), where we have obtained Hamilton-Jacobi equation (22).…”
Section: The Semiclassical Limit and The Highest Orders Of Expansionmentioning
confidence: 99%
“…In other approaches, the time derivative appears in equations of quantum geometrodynamics as a consequence of introducing a reference frame. In [9], the origin of time is introducing the Kuchař-Torre reference fluid [40]. This results in additional terms that can be combined to define a time derivative, which appears in the left-hand side of (18).…”
Section: Derivation Of the Temporal Schrödinger Equationmentioning
confidence: 99%
See 1 more Smart Citation